A biomechanical investigation of right-forward lunging step among badminton players - Mei, Q.; Gu, Y.; Fu, F.; Fernandez, J. (Journal of Sports Sciences, 2017)
This study presents the kinematics and plantar pressure characteristics of eight elite national-level badminton athletes and eight recreational college-level badminton players while performing a right-forward lunge movement in a laboratory-simulated badminton court. The hypothesis was that recreational players would be significantly different from elite players in kinematics and plantar pressure measures. Vicon® motion capture and Novel® insole plantar pressure measurement were simultaneously taken to record the lower extremity kinematics and foot loading during stance. Recreational players showed significantly higher peak pressure in the lateral forefoot (P = 0.002) and force time integral in the lateral forefoot (P = 0.013) and other toes (P = 0.005). Elite athletes showed higher peak pressure in the medial forefoot (P = 0.003), hallux (P = 0.037) and force time integral in the medial forefoot (P = 0.009). The difference in landing techniques for the lunge step between elite athletes and recreational players was observed with peak ankle eversion (-38.2°±2.4° for athletes and -11.1°±3.9° for players, P = 0.015); smaller knee range of motion in the coronal and transverse planes, with differences in peak knee adduction (28.9°±6.8° for athletes and 15.7°±6.2° for players, P = 0.031); peak knee internal rotation (20.3°±1.3° for athletes and 11.8°±3.2° for players, P = 0.029) and peak hip flexion (77.3°±4.1° for athletes and 91.3°±9.3° for players, P = 0.037).